Dynamics of transmission of Trypanosoma cruzi in a rural area of Argentina: III. Persistence of T. cruzi parasitemia among canine reservoirs in a two-year follow-up - Gurtler, Ricardo E.; Solard, Nora D.; Lauricela, Marta A.; Haedo, Ana S.; Pietrokovski, Silvia M.; Alberti, Andrea A.; Wisnivesky-Colli, Cristina (Revista do Instituto de Medicina Tropical de São Paulo, 1986)
A new cross-sectional survey of household- associated mongrel dogs as well as follow-up of previously parasitemic individuals was carried out in 1984 toy means of xenodiagnosis and serologic techniques to get a deeper insight into the relationship of T. cruzi parasitemia and age among canine hosts in a rural area of Argentina. Persistence of detectable parasitemia was age-independent, or at most, loosely related to age, confirming the pattern observed in 1982. Similarly no significant age-decreasing effect was recorded among seropositive dogs in: a) the probability of detecting parasites in a 2-year follow-up; b) their intensity of infectiousness (=infective force) for T. infestans 3rd-4th instar nymphs, as measured by the percentage of infected bugs observed in each dog xenodiagnosis. Moreover, not only was the infective force of seropositive dogs for bugs approximately constant through lifetime, but it was significantly higher than the one recorded for children in the present survey, and for human people by other researchers. Therefore, and since T. infestans field populations show high feeding frequencies on dogs, the latter are expected to make the greatest contribution to the pool of infected vectors in the rural household of Argentina. This characteristic should be sufficient to involve canine reservoirs definitely as a risk factor for human people residing in the same house. The increased severity of parasitemia observed among dogs in this survey may be related to the acute undernutrition characteristic of canine populations of poor rural areas in our country, which is expected to affect the ability of the host to manage the infection.